Crystallization of 2H and 4H PbI2 in carbon nanotubes of varying diameters and morphologies - Flahaut, E; Sloan, J; Friedrichs, S; Kirkland, A; Coleman, K; Williams, VC; Hanson, N; Hutchison, J; Green, M (2006)
The crystallization of the complex halide PbI2 in discrete and bundled single-walled carbon nanotubes (SWNTs), double-walled carbon nanotubes (DWNTs), and thicker walled nanotubes is described. The nanotubes were produced by either arc synthesis or catalytic chemical vapor deposition. The obtained crystals could be described in terms of ID fragments derived principally from the 2H form of PbI2, although some evidence for the formation of fragments derived from 4H PbI2 in some nanotubes was observed. The crystallization inside nanotubes was compared to the crystallization behavior of bulk PbI2 as determined by X-ray powder diffraction measurements obtained under comparable heating conditions. While the 2H to 4H polytype transition is clearly observable in bulk PbI2, stacking behavior correlated with this type of polytypism was only very occasionally observed within nanotubes, suggesting that crystallizing PbI2 within nanotubes has a tendency to order the halide into the 2H form. Additionally, PbI 2 apparently does not crystallize in rigid narrow DWNTs with internal diameters of less than 2 nm. Raman studies performed on the PbI 2-filled nanotubes show that the ratio of intensity of the D and G bands generally increases after filling and that both the RBM peaks and the G band are slightly upshifted. © 2006 American Chemical Society.